Ethnopornography : Sexuality, Colonialism, and Anthropological/Archival Knowledge - Tortorici, Zeb; Whitehead, Neil L.; Sigal, Pete; Tortorici, Zeb; Whitehead, Neil L.; Sigal, Pete (Duke University Press, 2020)
Ethnopornography collects essays that both develop and critique the concept that gives the book its name. Ethnopornography, a term first coined by British anthropologist Walter Roth in the late nineteenth century, refers to the often eroticized observation$1 (Bfor supposedly scientific or academic purposes$1 (Bof those deemed (3z(Bother(3y (Bby the observer. In Roth$1 (Bs case, he was concerned that the descriptions and images he recorded of the bodily and sexual practices of the Aboriginal people he studied were inappropriate for lay readers who might find them vulgar$1 (Bor worse, titillating. The editors of this collection focus on what it is that creates the slippage between the pornographic and the scientific. In particular, they attend to the importance of race within the colonially created and maintained worlds of both research$1 (Bethnography in particular$1 (Band pornography.s
Knowledge Unlatched
English
Keywords: Colonialism & imperialism; Political Science; Colonialism & Post-colonialism